AAZTA‐Like Ligands Bearing Phenolate Arms as Efficient Chelators for 68Ga Labelling in vitro and in vivo. Issue 21 (13th March 2023) - Martinelli, Jonathan; Zapelli, Leonardo Maria; Boccalon, Mariangela; Vágner, Adrienn; Nagy, Gábor; Fekete, Anikó; Szikra, Dezső; Trencsényi, György; Baranyai, Zsolt; Tei, Lorenzo
Abstract: The introduction of a phenolate pendant arm in place of an acetate on AAZTA‐ and DATA‐like ligands resulted in hepta‐ and hexadentate chelators able to form Ga(III) complexes with thermodynamic stability and kinetic inertness higher than that of other Ga(III) complexes based on the parent 6‐amino‐6‐methylperhydro‐1, 4‐diazepine scaffold. In particular, the heptadentate AAZ3A‐endoHB with a phenolate arm on an endocyclic N‐atom shows a log K GaL of 27.35 and a remarkable resistance to hydroxide coordination up to basic pH (pH>9). This behaviour allows to also improve the kinetic inertness of the complex showing a dissociation half‐life ( t 1/2 ) at pH 7.4 of 76 h. Although also the hexadentate AAZ2A‐exoHB chelator forms a stable (log K GaL =24.69) and inert ( t 1/2 =33 h at pH 7.4) Ga(III) complex, the 68 Ga labelling showed a better radiochemical yield with AAZ3A‐endoHB, especially at room temperature. Thus, a bifunctional chelator of AAZ3A‐endoHB was synthesized bearing an isothiocyanate group that was conjugated to the N‐terminus of a c(RGD) peptide for integrin receptor targeting. Finally, the conjugate was successfully labelled with 68 Ga isotope, and the resulting radiotracer tested for its stability in human serum and then in vivo for targeting B16‐F10 tumours with miniPET imaging. Abstract : AAZTA‐ and DATA‐like ligands bearing one phenolate pendant arm form Ga(III) complexes with significant thermodynamic stability and kinetic inertness. 68 Ga labelling was efficient both at room temperature and at 95 °C and an αv β3 integrin targeting probe was synthesized, labelled, and tested in vivo on B16‐F10 tumours.